Interdisciplinary Perspectives on Mortality and its Timings: When is Death? - Shane McCorristine (Palgrave Historical Studies in the Criminal Corpse and its Afterlife, 2017)
This volume provides a series of illuminating perspectives on the timings of death, through in-depth studies of Shakespearean tragedy, criminal execution, embalming practices, fears of premature burial, rumours of Adolf Hitler's survival, and the legal concept of brain death. In doing so, it explores a number of questions, including: how do we know if someone is dead or not? What do people experience at the moment when they die? Is death simply a biological event that comes about in temporal stages of decomposition, or is it a social event defined through cultures, practices, and commemorations? In other words, when exactly is death? Taken together, these contributions explore how death emerges in a series of stages that are uncertain, paradoxical, and socially contested.